Perlindungan Hukum Terhadap Warga Negara Asing dalam Perspektif Hukum Internasional - Agustina, Agustina; Ponto, Renaldi Timoti (Fakultas Syariah INSURI Ponorogo, 2023)
Residents of a country are citizens and non-citizens. People who are not citizens are called foreigners. The determination of whether a resident is a citizen or not is regulated by the national laws of each country. National laws determine who is a citizen. country. Regardless of his status as a citizen or foreigner, he is a subject of international law, has rights and obligations based on international law in a limited sense. In this limited sense, in contrast to the definition of states as subjects of international law in the full sense, when considering the issue of international legal protection of foreigners, an academic approach to the theory and practice of international courts is used. A foreigner has the right to equal protection under the laws of the country in which he resides reside and are also entitled to certain rights to opportunities for a decent life, as regulated in Article 9 of the Montevideo Convention of 1933 which reads: